A COMPATIVE STUDY OF TECHNICAL EFFICIENCY OF CERTIFED WHEAT CULTIVARS) ADNA 99 AND IPA 99) IN IRAQ DURING THE SEASON 2014-2015.(WASIT GOVERNORATE AS A CASE STUDY). - & Frhan, Al-Hachami (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
The cultivars planted are considered one of the important factors affecting the wheat production which work on increasing the productivity of the area unit. Therefore, the research aimed to measure the production efficiency of the exported Turkish wheat cultivar (ADNA 99) in comparing with Iraqi cultivar (IPa 99) for 2014-2015 seasons (Wasit governorate as a case study), based on the field data of a random sample from 84 farms in Wasit. The results showed the effect of the cultivar on the productivity and the inputs used via using the analysis of variance, it showed there is no significant differences between the two cultivars, in addition we have estimated the technical efficiency and the resources aechiving it were measured via using the Data Envelopment Analysis method of output oriented assuming variable return to scale which is in average were (0.69, 0.73) for (ADNA99) and (IPa 99) cultivars respectivly, in addition the results showed there is a waste in all the resources used. As a result there is no significant differences between the two cultivars, as well as the convergence of the results of technical efficiency and size resources achiving if therefore we recommend there is no need to import the cultivars (ADNA 9956) as well we recommend to indicative awareness to reduce wastage of resources using in production.